A Cross Sectional Study on Awareness and Knowledge of SARS CoV-2 and Vaccination among General Public - , K. Shailaja; , S. Benita; , G. Dinesh Kumar; , D. Harshidha; , M. V. Mousigan (Archives of Current Research International, 2022)
Background Information: COVID-19 is an infectious disease caused by the coronavirus SARS-CoV-2. The WHO declared it a global pandemic on March 12th, 2020. Government initiatives play a major role in limiting the spread of infection by educating people. Objectives: To assess the awareness and knowledge of COVID-19 and vaccination among general public. Methodology: A cross-sectional study as an online survey over a period of 6 months with 601 respondents. The information regarding the demographics was subjected to descriptive analysis. The study was conducted using a pre-tested semi-structured online Google form and a consent form obtained. Results: Among 601 participants, nearly 77% of respondents were practicing preventive measures. Nearly 68% of the respondent’s knowledge and awareness about the COVID-19 vaccination was in moderate level. Conclusion: During this pandemic, there were increased worries and apprehensions among the public regarding acquiring the COVID-19 infection. The disease is not eradicated completely, so it is necessary to educate the public continuously. It is not mandatory to stop the awareness-creating program, and advertising about the disease once the severity of the disease is reduced.